2010
DOI: 10.1590/s0365-05962010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Corno cutâneo: estudo histopatológico retrospectivo de 222 casos

Abstract: This study showed that the majority of cutaneosus horns occured in areas of the body that are exposed to the sun, predominantly head and upper limbs. Considering the high frequency of pre-malignant lesions and also the presence of malignant lesions it is suggested surgical exeresis followed by histopathological study of the cutaneous horns for confirmation of specific diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…A horn base may display benign or malignant histopathology. Horns with a benign histopathological base have a reported incidence ranging from 41% [1] to 60% [2, 3] and up to 77% on the eyelid [4]. Horn formation can occur in keratoacanthoma [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A horn base may display benign or malignant histopathology. Horns with a benign histopathological base have a reported incidence ranging from 41% [1] to 60% [2, 3] and up to 77% on the eyelid [4]. Horn formation can occur in keratoacanthoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…Horn formation can occur in keratoacanthoma [5]. Squamous cell carcinoma has been reported in 94% of horns with a malignant base [1]. Factors previously reported to be associated with premalignant and malignant horns are male sex, increased age, anatomic site and lesion geometry [2].…”
Section: Introductionmentioning
confidence: 99%
“…ese alternative methods of treatment are mostly preferred in cases where the lesion is small and there is low grade of suspicion of malignancy [12]. Sunscreens might have a preventive role in case of lesions commonly seen in the sun-exposed areas [9]. In our case, there was high suspicion of malignancy.…”
Section: Discussionmentioning
confidence: 63%
“…A study by Mantese et al also showed squamous cell carcinoma in 94% of the malignant lesions. ere was female preponderance in (64.86%) [9].…”
Section: Discussionmentioning
confidence: 99%
“…They differ from true animal horns in not having a bony core [2] [4]. The earliest documented case of cutaneous horn is from London in 1558 [5].…”
Section: Discussionmentioning
confidence: 99%